ON STANDARDIZATION OF RADIATION PROTECTION INDEXES OF NATURAL MINERAL WATERS - I. P. Stamat; V. V. Stupina (Радиационная гигиена)
Issues connected with the standardization of radiation protection indexes of natural mineral waters are considered in the article. It is shown that classification of natural mineral waters according to their intended use which is accepted in GOST R 54316-2011 is close to their classification in the EU countries. Justification is given of the approaches to standardization of natural radionuclides content in natural mineral waters. It is shown that it is more acceptable to use the values of interventional levels for individual radionuclides given in Radiation Safety Standard-99/2009 for this purpose in comparing with the values given in WHO Guidelines for Drinking-water Quality.